LECTURERS’ COMPETENCY FROM ISSUES TO THE FACTS - Rivi Antoni (English Study Program University of Pasir Pengaraian, 2015)
This research entitled lecturers’ competency from issues to the facts. The inconsistency of the quality of teaching and learning English became the first consideration to investigate the lecturers’ competency at English study program of University of Pasir Pengaraian. The researcher used descriptive quantitative design in investigating lecturers’ competency. To collect the data, questionnaires of lecturers’ competency were distributed to all lecturers. To analyze the data, the frequency score and percentage system were statistically operated. After collecting and analyzing the data, it was found that the pedagogical competency at 2.87 (closer to enough), Professional competency at 2.81 (closer to enough), Self-competency at 2.87(closer to enough) and Social competency at 3.31 (Enough). Finally, it could be concluded that lecturers’ competency in teaching English as a foreign language at English study program of University of Pasir Pengaraian were at average 2.96, categorized as Enough level of competency.